Estimates of the Cordoba - Fernandez operator in Marcinkiewicz spaces - Y. I. Berezhnoi; D. S. Gladkikh (Моделирование и анализ информационных систем, 2009)
In the A. Cordoba and P. Fernandez research of the divergence of greedy algorithms in Lebesgue spaces some maximum operator P*(x) played the key role. This article reviews the assessment P*(x) in Marcinkiewicz spaces.